UPAYA SATLANTAS POLRESTA PALANGKA RAYA DALAM MENCEGAH PEMALSUAN USIA OLEH PEMOHON PENERBITAN SIM C - Putra Mahardika Bagus M; Kiki Kristanto; Kristian Kristian; Putri Fransiska Purnama P (Jurnal Magister Hukum Perspektif, 2021)
To be able to have a driver's license for drivers of various types of vehicles must meet the conditions that have been set. Similarly, with driver's license C, one of the conditions that must be met is a minimum age of 17 years. It becomes a problem when the driver's license issuance applicant is a minor. Until now, there are still parents or applicants themselves who do the act of ageing to be able to issue a driver's license. In fact, Law No. 22 of 2009 concerning LLAJ and Perkapolri No. 9 of 2012 concerning driver's license has set the age limit allowed to apply for the issuance of driver's license C is 17 (seventeen) years. The formulation of the problem taken is what efforts are made by the Palangka Raya City Resort Police Traffic Unit to prevent age falsification by applicants for the issuance of a Two-Wheeled Motor Vehicle Driving License (driver's license C). This type of research uses juridical-empirical methods by looking at the application of rules in the field. The results found that the efforts made were to conduct law enforcement in the form of preventive approaches such as attaching additional conditions for applicants to issue new driver's license C indicated to be minors, the use of technological advances through the detection of NIK from driver's license C applicant ID cards online, as well as socialization through the installation of banners or banners in the Regident Satlantas Unit of Palangka Raya Police and through social media to prevent age falsification by reducing the age of the driver's license applicant. Keywords: Prevention Efforts, Age Falsification, driver's license C, Satlantas, Palangka Raya Police